Penerapan Metode Simple Additive Weigthing Untuk Menentukan Penerima Beasiswa KIP Kuliah Berbasis Web - Imam Hidayat; Dede Supriyadi (CV. Multi Kreasi Media, 2023)
KIP Lectures is an educational scholarship provided by the Government under the auspices of the Ministry of Education and Culture. This scholarship is intended for graduates of high school (SMA) or equivalent who have good academic potential and wish to continue their higher education but have economic limitations. In this study a decision support system will be applied using the web-based Simple Additive Weighting (SAW) method for receiving KIP scholarships for college. By using the SAW method, it is hoped that the results of this research will be obtained by prospective KIP scholarship recipients with accurate calculations because the SAW method will give a weight value to each criterion, besides that the simple calculation process can facilitate application in applications so that it will produce faster processing times.